Factors Affecting The Use Of E-Wallets Amongst You Gen Z Feb Unud Students - Ni Komang Maheswari Puspita Dewi Narendra Putri; I Made Pande Dwiana Putra (International Journal of Economics, Commerce, and Management, 2024)
E-Wallet is an application-based service that makes it easy for users to save money and use it as a payment method. This research aims to analyze the factors that influence e-wallet use among Gen Z FEB Unud students based on the Technology Acceptance Model (TAM) theory, which focuses on how perceived usefulness and perceived ease of use influence actual system use through behavioral intention as mediation. . The number of samples used was 203 respondents using the purposive sampling method . The research instrument used a questionnaire with a 5 point Likert scale . The collected data was then tested and analyzed using path analysis with the SPSS 21 program. The results of the research show that perceived usefulness and perceived ease of use have a positive and significant effect on actual system use through behavioral intention as a mediation of e-wallet use among Gen Z FEB Unud Student.